2016
DOI: 10.1111/tbed.12531
|View full text |Cite
|
Sign up to set email alerts
|

Dog Ecology and Barriers to Canine Rabies Control in the Republic of Haiti, 2014-2015

Abstract: An estimated 59 000 persons die annually of infection with the rabies virus worldwide, and dog bites are responsible for 95% of these deaths. Haiti has the highest rate of animal and human rabies in the Western Hemisphere. This study describes the status of animal welfare, animal vaccination, human bite treatment, and canine morbidity and mortality in Haiti in order to identify barriers to rabies prevention and control. An epidemiologic survey was used for data collection among dog owners during government-spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 24 publications
2
38
0
Order By: Relevance
“…Similar reports by ZDU-Kenya indicated that only 23% of owned dogs were routinely vaccinated in Makueni county [17, 18] while another study estimated that dog vaccination coverage in Kenya was 0.5% [3]. In tandem with the increased use of dogs as companion and guard animals in Kenya, the number of dog bites is likely to increase and as a result there will likely be an increase in rabies transmission especially in rural areas where dogs are not leashed and move freely thereby increasing the risk of exposure to rabies [1619]. …”
Section: Discussionmentioning
confidence: 99%
“…Similar reports by ZDU-Kenya indicated that only 23% of owned dogs were routinely vaccinated in Makueni county [17, 18] while another study estimated that dog vaccination coverage in Kenya was 0.5% [3]. In tandem with the increased use of dogs as companion and guard animals in Kenya, the number of dog bites is likely to increase and as a result there will likely be an increase in rabies transmission especially in rural areas where dogs are not leashed and move freely thereby increasing the risk of exposure to rabies [1619]. …”
Section: Discussionmentioning
confidence: 99%
“…When available, the vaccine in these centres is given free of charge, although there are often shortages. In 2014, for instance, Haiti received a sufficient stock of human rabies vaccines to treat 4000 people with suspected rabies exposure, yet an estimated 200 000 people experienced dog bites, 24 meaning that many suspected rabies exposures probably went untreated. Private pharmacies charge around US$12 per vaccine dose.…”
Section: Discussionmentioning
confidence: 99%
“…A 2014 survey estimated that 95,000 animal bites occur annually in Haiti (1% bite rate) ( 5 ). However, only 6,500 bites (6.8% of estimated bites) were reported through the national surveillance program that year.…”
Section: Discussionmentioning
confidence: 99%